2014
DOI: 10.1371/journal.pone.0092843
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lobeglitazone Monotherapy in Patients with Type 2 Diabetes Mellitus over 24-Weeks: A Multicenter, Randomized, Double-Blind, Parallel-Group, Placebo Controlled Trial

Abstract: ObjectiveThe aim of this study was to assess the glucose-lowering and lipid-modifying effects, and safety profile of lobeglitazone, a novel peroxisome proliferator-activated receptor- γ agonist, compared to placebo as a monotherapy in patients with type 2 diabetes.Research Design and MethodsIn this 24-week, multicenter, randomized, double-blind, parallel-group, placebo controlled study, 173 patients were randomly assigned (a 2∶1 ratio) to lobeglitazone 0.5 mg (n = 115) or matching placebo (n = 58) orally once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 18 publications
4
73
0
Order By: Relevance
“…Previous studies have shown that pioglitazone treatment increases body weight between 2.5 and 4.7 kg, depending on the study (23)(24)(25). In our study, lobeglitazone treatment showed a lower increase in the average body weight of 1.4 kg (from 76.5 ± 11.1 kg to 77.9 ± 11.8 kg [P = 0.001]), which is similar to the weight gain, ranging from 0.89 to 1.48 kg, that was observed in other clinical trials using 0.5 mg/day lobeglitazone (15)(16)(17).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have shown that pioglitazone treatment increases body weight between 2.5 and 4.7 kg, depending on the study (23)(24)(25). In our study, lobeglitazone treatment showed a lower increase in the average body weight of 1.4 kg (from 76.5 ± 11.1 kg to 77.9 ± 11.8 kg [P = 0.001]), which is similar to the weight gain, ranging from 0.89 to 1.48 kg, that was observed in other clinical trials using 0.5 mg/day lobeglitazone (15)(16)(17).…”
Section: Discussionsupporting
confidence: 85%
“…Recently, a novel TZD called lobeglitazone was developed, and is currently being prescribed for T2D in Korea (14). The efficacy and safety of lobeglitazone in T2D has been well-investigated (15)(16)(17). To identify better treatment options for T2D patients with NAFLD, we investigated the effects of lobeglitazone on these patients by analyzing alterations in their CAP values using transient liver elastography, as well as in their glycemic, lipid, and liver profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Phase III clinical trial data show that lobeglitazone treatment resulted in an approximately 0.6% to 0.74% decrease in glycated hemoglobin compared with that of the placebo [1617]. It is administered as a once-daily dose and mainly excreted in feces, reducing concerns of bladder cancer unlike the classic TZD pioglitazone.…”
Section: Introductionmentioning
confidence: 99%
“…It does not mean that these dual PPAR α and PPAR γ agonists have no side effects. For example, weight gain was still observed in lobeglitazone-treated diabetic subjects [50]. Collectively, existing evidence suggests that the usage of dual PPAR α and PPAR γ agonists was relatively well tolerated and acceptable considering the balance between efficacy and side effects.…”
Section: Transcriptional Regulation Of Ppars In White Brown and mentioning
confidence: 99%